Developing Calligraphic Courtesan Script. Handwriting and Printing connection in Segovia during the Fifteenth century - Valero Eduardo Juárez (De Gruyter, 2021)
During the investigation of the Research Group Señoríos Medievales Segovianos in the Archive of the Diocese of Segovia an unusual document was digitized. It was a building license for Bishop Juan Arias Dávila to improve University facilities. This document was written in a different script: The Calligraphic Courtesan Script. related to traditional Courtesan script; this document was written in an especially clear writing style not connected with the usual cursive gothic styles in Castilla. This article tries to connect this clearness in the writing style with the presence of Juan Parix from Heidelberg in Segovia, who brought the first Spanish printing press to Segovia.